Letter to CSU Northridge from Robert Chianese - Sustainability Council of Ventura County; Chianese, Robert
Letter from Robert Chianese to CSU Northridge requesting reimbursement for expenses on the California Urban Environmental Research and Education Center (CUEREC) funded project entitled Impacts of Urban Growth Limits on the Environment and Quality of Life in Ventura County that totals for $3,694.00